A phytochemical study of scabiosa atropurpurea family dipsacaceae cultivated in Egypt - Nashwa Moheyeldine Mohamed; Hossam Abdallah; Mona Elmahdy; Seham Elhawary (Cairo : Nashwa Moheyeldine Mohamed, 2012)
Family Dipsacaceae is a small family comprising of about 150 species distributed among 8 genera . It is distributed mainly in Europe , Asia , Africa , but espcially Mediterranean region . Scabiosa atropurpurea L. traditionally known as Ambarina in Northern Peru and as Escabiosa in north - east Catalonia ( Iberian Peninsula ) has been used traditionally for its antibacterial activity in bronchitis , for menstrual regulation and as veterinary diuretic
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Family dipsacaceae; Phytoconstituents; Scabiosa atropurpurea